2022
DOI: 10.1186/s12884-022-04702-2
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of maternal role adaptation in Iranian women: a cross-sectional study

Abstract: Background Numerous factors play a role in maternal identity formation and function. Recognizing the aspects related to adaptation to the mother role can effectively provide a solution to help mothers construct maternal roles. Consequently, this study aimed to determine the predictors of adaptation to the maternal role in Iranian women. Methods This cross-sectional study was performed on 564 women who gave birth within one to four months after deli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…Indeed, other studies have identified that; number of births, birth experience, type of birth, and maternal and neonatal complications influence postpartum maternal performance in the general population [23,43]. Moreover, parents whose babies were admitted to the intensive care unit have been found to have a higher adaptation score with the maternal role, and those who had full-term babies have been found to have a higher adaptation score with the maternal role compared to mothers who had preterm babies [44] Numerous other variables including maternal age, perception of the childbirth experience, preterm childbirth, social stress, social support, and personality traits in the formation of maternal identity and functioning have been found to affect maternal adjustment, including social and psychological factors [43][44][45].Those with high-risk pregnancies may experience multiple hospitalizations during pregnancy, which may also lead people to experience different emotions [45]. Thus in the long term, those who experience high-risk pregnancies may experience depression or PTSD.…”
Section: Discussionmentioning
confidence: 98%
“…Indeed, other studies have identified that; number of births, birth experience, type of birth, and maternal and neonatal complications influence postpartum maternal performance in the general population [23,43]. Moreover, parents whose babies were admitted to the intensive care unit have been found to have a higher adaptation score with the maternal role, and those who had full-term babies have been found to have a higher adaptation score with the maternal role compared to mothers who had preterm babies [44] Numerous other variables including maternal age, perception of the childbirth experience, preterm childbirth, social stress, social support, and personality traits in the formation of maternal identity and functioning have been found to affect maternal adjustment, including social and psychological factors [43][44][45].Those with high-risk pregnancies may experience multiple hospitalizations during pregnancy, which may also lead people to experience different emotions [45]. Thus in the long term, those who experience high-risk pregnancies may experience depression or PTSD.…”
Section: Discussionmentioning
confidence: 98%